Large scope business sector reforms: Has the Swedish business sector become more entrepreneurial than the U.S. business sector? - Fredrik Andersson; Fredrik Heyman; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2016)
Recent studies document a 30-year decline in various measures of entrepreneurship in the United States. In contrast, using detailed Swedish employer-employee data over the period 1990-2013, we find no decline in Swedish entrepreneurial activity. Aggregate net job creation is greatest among the youngest firms in the Swedish business sector. Moreover, most of the net job creation by young firms takes place in the expanding service sector. We argue that a key explanation for the high entrepreneurial activity in the Swedish business sector during the last two decades stems from economic reforms in the 1990s that mitigated several hurdles to entrepreneurship.
Keywords: J23; K23; L26; L51; 330; Entrepreneurship; Job dynamics; Matched employer-employee data; Industrial structure and structural change